Find the implicit solution to the folling DE:

$(2xy^2+3y)dx+(3x^2y+2x)dy=0$; with a starting condition $y(1)=\frac 1 2$

I can fight myself to the integrating factor.


$\mu(x,y)= \frac 1 {xy(1-xy)}$ giving us the following exact DE: $$\frac{2xy+3}{x(1-xy)}dx+\frac{3xy+2}{y(1-xy)}dy=0$$

Testing $$(\mu P)_y=\frac{2x(x(1-xy)+(2xy+3)x^2}{x^2(1-xy)^2}="some-brute-force-magicks"=\frac{1}{(1-xy)^2}$$

$$(\mu Q)_x=\frac{3y(1-xy)y-(3xy+2)y(-y)}{y^2(1-xy)^2}=\frac{1}{(1-xy)^2}$$

Thus $(\mu P)_y=(\mu Q)_x$

From here I try to get $u=?$ $$u=\int(\mu P)dx=\int\frac{2xy+3}{x(1-xy)}dx=3ln(x)-5ln(1-xy)+C(y)$$

So far so good but ...now ...either this so far is wrong in theory, I messed up my integration, or I keep misscalculating my deritative as my calculation $u_y \neq (\mu Q)$

I tried (whats the English word) rearranging (?) $$u=ln \left(\frac{x^3}{(1-xy)^5} \right)+C$$

Help would be nice.

  • 1
    $\begingroup$ $u$ is correct, but write $C(y)$ as $N(y)$. Now, take the derivative of $u_y$ and substitute $\dfrac{3xy+2}{y(1-xy)}$ and solve for $N$. $\endgroup$ – Moo Feb 12 '17 at 2:34
  • $\begingroup$ @Moo The thing is if I compare my $u_y$ to $(\mu Q)$ I get such a disgusting value for $C'(y)$ So im not sure if I should have put C under the log via $u=log(...)+logC(y)$ or not. On top of that I'm not fully sure how to even get to the $y(x)$ from here on to even enter the boundry condition of $y(1)=1/2$ in $\endgroup$ – Katpton Liamfuppinshire Feb 12 '17 at 3:21
  • $\begingroup$ I added an answer wit more details. $\endgroup$ – Moo Feb 12 '17 at 3:22


$$\tag 1 M(x, y)~ dx + N(x, y)~ dy = (2xy^2+3y)~dx+(3x^2y+2x)~dy=0,y(1)=\dfrac 1 2$$

You found an integrating factor that makes $M_y = N_x$ as

$$\tag 2 \mu(x,y)= \dfrac 1 {xy(1-xy)}$$

Multiplying $(1)$ by $(2)$ gives the exact DEQ

$$\tag 3 \dfrac{2xy+3}{x(1-xy)}dx+\dfrac{3xy+2}{y(1-xy)}dy=0$$


$$g(x, y) = \displaystyle \int \left(\dfrac{2xy+3}{x(1-xy)}\right)~dx = 3 \ln x - 5 \ln(1 - x y) + h(y)$$

We can now write

$$\dfrac{\partial g(x, y)}{\partial y} = \dfrac{5 x}{1-x y } + h'(y) = \dfrac{3xy+2}{y(1-xy)} \implies h'(y) = \dfrac{3xy+2}{y(1-xy)} - \dfrac{5 x}{1-x y } = \dfrac{2}{y}$$


$$h(y) = 2 \ln y$$

We now have

$$g(x, y) = 3 \ln x - 5 \ln(1 - x y) + h(y) = 3 \ln x - 5 \ln(1 - x y) + 2 \ln y = c$$

I will assume you can take it from here to solve for $c$ using the IC and get the final implicit form.

  • $\begingroup$ Hmmm ya i noticed where i did my mistake. And it was always the same when i tried calculating $g_y$ So from here I can simply enter $x=1$ and $y=\frac1 2$ ? To get my C out of this? Might stuggle a bit with the implicit form here. Was never good at this part. EDIT: And thanks, now I can finally try and get some sleep. $\endgroup$ – Katpton Liamfuppinshire Feb 12 '17 at 3:27
  • 1
    $\begingroup$ Yes, just sub in those values of $x$ and $y$, get $c$ and you are done. The solution is already in implicit form - just find $c$ and replace in the implicit form solution. $\endgroup$ – Moo Feb 12 '17 at 3:29

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.